2021
DOI: 10.3389/fpubh.2021.759160
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime and 1-Month Prevalence of Mental Disorders in Hebei Province, China: A Community-Based Cross-Sectional Study

Abstract: Background: The prevalence of mental disorders is an important topic, which has been reported in different countries in the world. In China, some studies were also conducted to get the prevalence of mental disorders at the national level and in some metropolitan cities. However, the prevalence of mental disorders in Chinese underdeveloped provinces has not been reported internationally in recent decades. Due to the discrepancy in the social-economic development of different Chinese provinces, we also have reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…China has witnessed unprecedented urbanization and associated rural depopulation over the past 40 years, along with a huge increase in the total population (10,11). The rapid migration and urbanization process in China has led to pronounced changes in community composition and its characteristics (12), evoking great scholarly interest in the effects of urbanization on mental health for Chinese people (13)(14)(15)(16)(17)(18). Most studies suggested an inverse relationship between urbanization and mental health (14,16,19), with urban living related to a lower prevalence of developing mental health problems (such as schizophrenia, dementia, cognitive impairment, and mood disorders) (14,16,17).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…China has witnessed unprecedented urbanization and associated rural depopulation over the past 40 years, along with a huge increase in the total population (10,11). The rapid migration and urbanization process in China has led to pronounced changes in community composition and its characteristics (12), evoking great scholarly interest in the effects of urbanization on mental health for Chinese people (13)(14)(15)(16)(17)(18). Most studies suggested an inverse relationship between urbanization and mental health (14,16,19), with urban living related to a lower prevalence of developing mental health problems (such as schizophrenia, dementia, cognitive impairment, and mood disorders) (14,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid migration and urbanization process in China has led to pronounced changes in community composition and its characteristics (12), evoking great scholarly interest in the effects of urbanization on mental health for Chinese people (13)(14)(15)(16)(17)(18). Most studies suggested an inverse relationship between urbanization and mental health (14,16,19), with urban living related to a lower prevalence of developing mental health problems (such as schizophrenia, dementia, cognitive impairment, and mood disorders) (14,16,17). Especially residence in highly urbanized areas was associated with lower depressive symptoms (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation